2001
DOI: 10.1016/s0014-5793(01)03088-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of β‐defensin‐2 by human colonic epithelial cells induced by Salmonella enteritidis flagella filament structural protein

Abstract: 2+ or pertussis toxin. The FliC-induced increase in hBD-2 promoter activity via nuclear factor U UB (NF-U UB) was also inhibited by chelation of intracellular Ca 2+ or by U73122. We conclude that FliC increased [Ca 2+ ] in via inositol 1,4,5-trisphosphate, which was followed by up-regulating hBD-2 mRNA expression via an NF-U UB-dependent pathway. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 32 publications
2
44
0
1
Order By: Relevance
“…The increase in ␤-defensin-2 expression correlates with an increase in the related ␤-defensin-3 but does not correlate with expression of TNF-␣, suggesting that other factors are involved in its regulation (28). Our coauthors have demonstrated that Salmonella enteritidis flagellin increases ␤-defensin-2 promoter activation in IEC (26,29). Human ␤-defensin gene expression is increased in tracheobronchial epithelial cells in response to LPS (30) and in lung and skin epithelial cells in response to TLR2 stimulation (31)(32)(33)(34).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The increase in ␤-defensin-2 expression correlates with an increase in the related ␤-defensin-3 but does not correlate with expression of TNF-␣, suggesting that other factors are involved in its regulation (28). Our coauthors have demonstrated that Salmonella enteritidis flagellin increases ␤-defensin-2 promoter activation in IEC (26,29). Human ␤-defensin gene expression is increased in tracheobronchial epithelial cells in response to LPS (30) and in lung and skin epithelial cells in response to TLR2 stimulation (31)(32)(33)(34).…”
mentioning
confidence: 85%
“…␤-Defensins are synthesized by various epithelial cells such as in the skin, respiratory tract, and gastrointestinal tract (24,25). Whereas expression of human ␤-defensin-1 may be constitutive, ␤-defensin-2 is induced by bacterial infection (26,27).…”
mentioning
confidence: 99%
“…Because FliC is reported to activate the NF-kB pathway in epithelial cells Reed et al, 2002;Takahashi et al, 2001) and because the NF-kB pathway participates in the induction of SOCS-3 expression (Hayashi et al, 2002), we investigated the participation of the NF-kB signalling pathway in SPI-2-dependent expression of SOCS-3. As shown in Fig.…”
Section: Detection Of Flic In Salmonella-infected Macrophagesmentioning
confidence: 99%
“…In vitro experiments show that hBD1 is constitutively expressed and that its production is not influenced by bacterial exposure, while other hBDs are inducible when exposed to bacteria [67,[72][73][74][75]. In particular, hBD2, first identified from skin [8], is highly responsive to bacteria, pro-inflammatory stimuli (IL−1β, TNFα, LPS), and phorbol myristate acetate [63,72,74,[76][77][78][79]. Previous reports show that hBD1 and hBD2 have strong antibacterial activity against Gram-negative bacteria and weak (or no) activity against Gram-positive bacteria, while hBD3 and hBD4 have strong activity against both Gram-positive and Gram-negative bacteria [8,41,50,61,66,[80][81][82][83].…”
Section: Defensinsmentioning
confidence: 99%